Facilitators and Barriers in Australian Disability Housing Support Policies: Using a Human Rights Framework - Sarah Parker; Karen Fisher (Disability Studies Quarterly, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; mso-bidi-font-size:10.0pt; font-family:"Arial","sans-serif"; mso-fareast-font-family:Arial; mso-bidi-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>What prevents people with disabilities from having their right to housing support fulfilled? The article identifies the facilitators and barriers to adequate housing support in Australia for people who need 24-hour support by applying a human rights framework to analyze Australian disability housing support policies. The article provides an overview of approaches to housing support arrangements. It outlines the primary goals of disability housing support from disability theory and policy as encompassing human rights, quality of life, independent living and cost effectiveness. The research provides insight into the right of people with disabilities to housing support in a changing policy context and it identifies seven key facilitators and barriers to fulfilling the right to disability housing support: (1) legislation, agreements and regulations; (2) funding and demand management; (3) interagency coordination; (4) range, flexibility and choice of housing support; (5) staffing quality; (6) informal carers; and (7) discrimination.
Keywords: Disability; Housing; Human Rights; Social Policy; Support Services; Australia